Nitrate Sensing and Metabolism Inhibit Biofilm Formation in the Opportunistic Pathogen Burkholderia pseudomallei by Reducing the Intracellular Concentration of c-di-GMP - Mangalea, Mihnea R.; Plumley, Brooke A.; Borlee, Bradley R. (Frontiers in Microbiology, 2017)
The opportunistic pathogen Burkholderia pseudomallei is a saprophytic bacterium and the causative agent of melioidosis, an emerging infectious disease associated with high morbidity and mortality. Although melioidosis is most prevalent during the rainy season in endemic areas, domestic gardens and farms can also serve as a reservoir for B. pseudomallei during the dry season, in part due to irrigation and fertilizer use. In the environment, B. pseudomallei forms biofilms and persists in soil near plant root zones. Biofilms are dynamic bacterial communities whose formation is regulated by extracellular cues and corresponding changes in the nearly universal secondary messenger cyclic di-GMP. Recent studies suggest B. pseudomallei loads are increased by irrigation and the addition of nitrate-rich fertilizers, whereby such nutrient imbalances may be linked to the transmission epidemiology of this important pathogen. We hypothesized that exogenous nitrate inhibits B. pseudomallei biofilms by reducing the intracellular concentration of c-di-GMP. Bioinformatics analyses revealed B. pseudomallei 1026b has the coding capacity for nitrate sensing, metabolism, and transport distributed on both chromosomes. Using a sequence-defined library of B. pseudomallei 1026b transposon insertion mutants, we characterized the role of denitrification genes in biofilm formation in response to nitrate. Our results indicate that the denitrification pathway is implicated in B. pseudomallei biofilm growth dynamics and biofilm formation is inhibited by exogenous addition of sodium nitrate. Genomics analysis identified transposon insertional mutants in a predicted two-component system (narX/narL), a nitrate reductase (narGH), and a nitrate transporter (narK-1) required to sense nitrate and alter biofilm formation. Additionally, the results presented here show that exogenous nitrate reduces intracellular levels of the bacterial second messenger c-di-GMP. These results implicate the role of nitrate sensing in the regulation of a c-di-GMP phosphodiesterase and the corresponding effects on c-di-GMP levels and biofilm formation in B. pseudomallei 1026b.